THE MICROBIAL ETIOLOGY AND ANTIBIOTIC SUSCEPTIBILITY PATTERN OF URINARY TRACT INFECTION IN ANTENATAL WOMEN IN A TERTIARY CARE CENTRE - Khan, Anjum; Nonhare , Nitigya; Dhruw, Shweta Singh (International Journal of Pharma and Bio Sciences, 2025)
Urinary tract infection is defined as growth of a significant number of organisms. Occurrence of asymptomatic bacteriuria (ASB) in pregnant women is a major predisposition to the development of pyelonephritis, which is associated with significant maternal and fetal complications. Therefore, the present study was conducted to study microbial etiology and antibiotic susceptibility patterns of UTI in pregnancy. The study was designed as a hospital-based, prospective Observational study conducted at the Department of Obstetrics and Gynecology in Pt. J.N.M. Medical College and Dr. BRAM Hospital in Raipur, Chhattisgarh. The study spanned from July 2022 to August 2023. The study subjects included asymptomatic pregnant women identified with pus cells in the screening test (Urine routine microscopy) and symptomatic pregnant women seeking care. The statistical software namely SPSS 22.0 used for the analysis of the data. The majority of the patients were in the age group 26-30 years (40%) with mean age was 26.39 ±4.38 years. The maximum number of patients infected with E coli. (78.75%) The maximum number of patients among gram positive infection 95% had enterococcus. The antibiotic sensitivity among gram positive isolates showed that Enterococcus was maximum sensitive to Linezolid (100%). The present study underscores the critical importance of routine UTI screening during pregnancy. The majority of UTIs during pregnancy are caused by gram-negative bacteria such as E. coli.